2013
DOI: 10.1371/journal.pone.0074299
|View full text |Cite
|
Sign up to set email alerts
|

The Role of N-Glycosylation in Folding, Trafficking, and Functionality of Lysosomal Protein CLN5

Abstract: CLN5 is a soluble lysosomal protein with unknown function. Mutations in CLN5 lead to neuronal ceroid lipofuscinosis, a group of inherited neurodegenerative disorders that mainly affect children. CLN5 has eight potential N-glycosylation sites based on the Asn-X-Thr/Ser consensus sequence. Through site-directed mutagenesis of individual asparagine residues to glutamine on each of the N-glycosylation consensus sites, we showed that all eight putative N-glycosylation sites are utilized in vivo. Additionally, local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 33 publications
2
78
0
Order By: Relevance
“…N-Glycosylation is a key post-translational process that facilitates protein folding, intracellular trafficking, secretion, and cell surface expression (42)(43)(44)(45). In type II transmembrane serine proteases, N-glycans are important for the cell surface targeting and zymogen activation of corin, a protease that regulates salt-water balance and blood pressure (34,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…N-Glycosylation is a key post-translational process that facilitates protein folding, intracellular trafficking, secretion, and cell surface expression (42)(43)(44)(45). In type II transmembrane serine proteases, N-glycans are important for the cell surface targeting and zymogen activation of corin, a protease that regulates salt-water balance and blood pressure (34,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Mature normal CLN5 protein is primarily located in the lysosomes [41,43,44]. As the human CLN5 propeptide passes through the golgi apparatus on its way to the lysosomes, it acquires mannose-rich oligosaccharides at all 8 of its N-glycosylation consensus sequences [45]. Site-directed mutagenesis experiments with the human gene suggested that the glycosylation of at least 6 of these sites is required for normal protein function [45].…”
Section: Mutant Cln5 Proteinmentioning
confidence: 99%
“…As the human CLN5 propeptide passes through the golgi apparatus on its way to the lysosomes, it acquires mannose-rich oligosaccharides at all 8 of its N-glycosylation consensus sequences [45]. Site-directed mutagenesis experiments with the human gene suggested that the glycosylation of at least 6 of these sites is required for normal protein function [45]. Glycosylation at the furthest C-terminal of these sites was required for normal trafficking to the lysosomes [45].…”
Section: Mutant Cln5 Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Human CLN5 consists of 407 amino acids with an N-terminal signal sequence that is cleaved in the ER co-translationally [19]. In human CLN5 there are eight N-glycosylation consensus sites (N-X-T/S) present (Asparagine residues on position 179, 192, 227, 252, 304, 320, 330, and 401) and all are utilized, with roles involving proper folding, lysosomal targeting and function [20]. A previous study showed CLN5 contains a C-terminal amphipathic helix region that is tightly associated with the membrane [21].…”
Section: Introductionmentioning
confidence: 99%